Household-income trajectories and mental health inequalities in Germany before, during, and after the COVID-19 pandemic: a quasi-experimental panel study - Ibrahim Demirer; Heike Krüger; Timo-Kolja Pförtner (International Journal for Equity in Health)
Abstract Background The COVID-19 pandemic disrupted progress toward achieving the Sustainable Development Goals (SDGs), particularly SDG 10 (Reduced Inequalities) and SDG 3 (Good Health and Well-Being). In Germany, labor market volatility, compounded by record inflation, widened social inequalities and contributed to a gradient in mental health. This study examines the relationship between household income and mental health before, during, and after the pandemic in the German working population, addressing whether mental health burdens persisted post-pandemic. Methods Using the German Socioeconomic Panel (v39.0), we applied a quasi-experimental design employing a ‘placebo control’ approach to obtain difference-in-difference (DiD) estimates. For this purpose, we created an ‘intervention’ sample consisting of respondents exposed to the COVID-19 pandemic (N = 8,340, 2018–2022) and a ‘placebo control’ sample, consisting of respondents not exposed to the COVID-19 pandemic (N = 11,869, 2014–2018), designed to mimic the intervention sample. Sequence analysis identified six typical household income trajectories (S1–S6): high, regular, fluctuating-I-II, low and unemployed. We used estimation methods to assess the mental health impacts of these trajectories during and post-pandemic, stratified by gender. Results The results confirmed a strong social gradient in mental health tied to household income. For males, the COVID-19 pandemic caused a mental health decline of ~ ¼ standard deviation for trajectories reflecting regular (S2), fluctuating (S3), and low household income (S5) (e.g., S3-DiD = -2.043**), while those in high household income or unemployed trajectories were unaffected. Females experienced a more generalized mental health decline across all trajectories. Post-pandemic, mental health showed signs of recovery but did not fully return to pre-pandemic levels. Conclusions These findings revealed that regular and fluctuating household income trajectories (S2–S5) are particularly vulnerable to mental health impacts during crises. Females are disproportionately affected, highlighting the need for targeted public health interventions. Strengthening institutional supports, such as childcare, and addressing gender disparities can help build resilience and advance progress toward the SDGs.